2015
DOI: 10.1590/s1806-37132015000100008
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of the Bedside Lung Ultrasound in Emergency protocol for the diagnosis of acute respiratory failure in spontaneously breathing patients,

Abstract: Objective: Bedside lung ultrasound (LUS) is a noninvasive, readily available imaging modality that can complement clinical evaluation. The Bedside Lung Ultrasound in Emergency (BLUE) protocol has demonstrated a high diagnostic accuracy in patients with acute respiratory failure (ARF). Recently, bedside LUS has been added to the medical training program of our ICU. The aim of this study was to investigate the accuracy of LUS based on the BLUE protocol, when performed by physicians who are not ultrasound experts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 24 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…Many studies enrolled patients with suspected pneumonia/community-acquired pneumonia, acute dyspnea, or acute respiratory failure. In some studies that enrolled patients with acute dyspnea or acute respiratory failure, cardiac ultrasound and/or leg vein compression ultrasound was performed in addition to LUS to evaluate pneumonia and other pathologies causing these signs [ 9 , 51 , 53 , 54 , 57 59 ]. The majority of the studies considered an LUS examination to be positive if signs of sonographic consolidation and/or focal multiple B-lines were observed.…”
Section: Image Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies enrolled patients with suspected pneumonia/community-acquired pneumonia, acute dyspnea, or acute respiratory failure. In some studies that enrolled patients with acute dyspnea or acute respiratory failure, cardiac ultrasound and/or leg vein compression ultrasound was performed in addition to LUS to evaluate pneumonia and other pathologies causing these signs [ 9 , 51 , 53 , 54 , 57 59 ]. The majority of the studies considered an LUS examination to be positive if signs of sonographic consolidation and/or focal multiple B-lines were observed.…”
Section: Image Acquisitionmentioning
confidence: 99%
“…Amatya et al [ 29 ] reported that the sensitivity and specificity were 91% and 61%, and Sezgin et al [ 40 ] reported that the sensitivity and specificity were 98% and 96%, respectively. Several studies conducted in the ICU setting showed that the sensitivity ranged from 88% to 97%, and the specificity ranged from 50% to 94% [ 9 , 47 , 50 , 53 ]. Some studies showed a small number of false-positive results in patients with neoplasia [ 26 , 30 , 31 , 52 ], atelectasis [ 27 , 31 ], pulmonary infarction [ 30 , 52 ], abscess [ 27 ], congestive heart failure [ 52 ], chronic obstructive pulmonary disease [ 52 ], and fibrotic band [ 31 ].…”
Section: Image Acquisitionmentioning
confidence: 99%
“…Anile et al, using LUS, demonstrated good correlation between the number of lung areas positive for B-lines and extravascular lung water [20]. Many studies have assessed the utility of LUS as a semi-quantitative score to measure the lung aeration loss caused by different lung pathologic features in patients with shock, acute respiratory failure, overhydration from nephrology, cardiologic pathologies, and patients that are critically ill [11,17,21,22,23,24,25,26,27,28]. For chronic diseases, studies have demonstrated the utility of LUS as a screening tool to evaluate ILD in connective tissue diseases (CTDs) [10,14,18,29,30,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…In the intensive care setting, Dexheimer Neto et al, 32 using the BLUE protocol in dyspneic patients, have found an 84% agreement between PU and the final diagnosis of pneumonia or acute pulmonary edema (total kappa = 0.81). Yamanoglu et al 33 have detected the cardiac origin of dyspnea by using the caval index (sensitivity= 84.4% and specificity= 92.9%).…”
Section: Resultsmentioning
confidence: 99%